Pewarisan ilmu dukun dalam sistem penyembuhan tradisional - Nur Ika Anisa' Ul Jannah; Siti Zurinani (Faculty of Social and Political Science, Universitas Airlangga, 2017)
People in Sidodadi village believe that shaman and their shamanic power have ability to heal health problems. However, a shaman is usually reluctant to be called „shaman‟ since the term of shaman is highly associated with a form of black magic. They prefer to be called „tyang saget‟ (capable people). This research focuses to describe shamanic power inheritance within shaman practice in Sidodadi village. Understanding the shamanic power inheritance is part of the way to understand reasons of people of Sidodadi who still believe in shaman. This research was conducted in Sidodadi village, in north Banyuwangi, East Java. This research used snowball sampling technique to enrich qualitative data and to strengthen the argument. Data gathered by direct observation of shaman related activities of Sidodadi people. Thus, data analyzed used descriptive ethnographic method. The result shows that familial ties dominate the shamanic power inheritance. There is a cycle where shaman in Sidodadi transfers their knowledge to their descendant whom believed would take the role as shaman in the future.